2016
DOI: 10.1007/s11655-016-2498-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Danhong Injection (丹红注射液) and its main components on anticoagulation and fibrinolysis in cultured vein endothelial cells

Abstract: Danhong Injection and its main components played an important role in protecting primary VECs from hypoxic damage by regulating the secretion and vasomotor function of VECs. The function of Danhong Injection was most remarkable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Although the pleiotropic effects of DHI on both cardio- and cerebral vasculatures are in accordance with the holistic concept of TCM, they also posed a great challenge in identifying individual chemical compounds responsible for the diverse pharmacological mechanisms. Previous studies by us and others have reported certain major active ingredients of DHI, such as phenolic acids, diterpenes and flavonoids, including salvianolic acid B, danshensu, caffeic acid, rosmarinic acid, kaempferol, protocatechuic acid and hydroxysafflor yellow A 51 , 53 , 54 , 58 , 62 68 .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although the pleiotropic effects of DHI on both cardio- and cerebral vasculatures are in accordance with the holistic concept of TCM, they also posed a great challenge in identifying individual chemical compounds responsible for the diverse pharmacological mechanisms. Previous studies by us and others have reported certain major active ingredients of DHI, such as phenolic acids, diterpenes and flavonoids, including salvianolic acid B, danshensu, caffeic acid, rosmarinic acid, kaempferol, protocatechuic acid and hydroxysafflor yellow A 51 , 53 , 54 , 58 , 62 68 .…”
Section: Introductionmentioning
confidence: 87%
“…(2) Basic researches indicate that DHI can ameliorate cerebral ischemia-reperfusion injury 40 43 , cerebral ischemia damage 44 , myocardial reperfusion injury 45 , 46 , myocardial hypertrophy 47 , cardiac dysfunction 48 and cardiac ventricular remodeling 48 . (3) Pharmacological actions of DHI include antioxidation 49 , 50 , anticoagulation 51 , anti-inflammatory 52 54 , anti-fibrosis 55 , anti-angiogenesis 55 , anti-atherosclerosis 56 and anti-diabetes 57 effects. It is also capable of promoting vasodilation 58 , inhibiting vasoconstriction 59 and hyperlipidemia 60 .…”
Section: Introductionmentioning
confidence: 99%
“…This study investigated the pharmacokinetic analysis of single and combined medication of PAL and HSYA, which are the 2 main parts of DHI. The previous studies have shown the pharmacokinetics of PAL and HSYA by using them either alone or combined with other drugs in normal rats [24][25][26]. The corresponding mechanism of the single and combined application in hyperlipidemia model, however, has not been reported.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, DHI reduces hypoxia-induced damage in venous endothelial cells. Compared with the hypoxic group, DHI increases levels of 6-keto-PGF1α and NO, as well as the activity of SOD and t-PA , and decreases levels of endothelin-1 (ET-1) and MDA, PAI activity, as well as the apoptosis rate [117].…”
Section: Experimental Studies and Molecular Mechanismsmentioning
confidence: 89%